PENGARUH FAKTOR INTI NILAI TUKAR DAN DAYA SAING TERHADAP TERM OF TRADE SERTA DAMPAKNYA KEPADA DAYA BELI MASYARAKAT INDONESIA - Francisca Sestri Goestjahjanti (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2016)
The purpose of this reseach is to examine and analyze the influence of exchange rate and competitiveness core factors of the Term of trade in Indonesia, also the impact on the people’s purchasing power in Indonesia. This research used secondary data time series for 21 years since 1995 to 2015. The research method used explanatory research to explain the causal relationship between the variables in a model, through hypothesis testing. The analyzes employed statistical technique of linear regression with the software E-Views 7.The results of the researchs showed that these core factors exchange rate and competitiveness are simultaneously and partially give positive and significant effect on term of trade in Indonesia. Term of trade also gives positive and significant that influence the people’s purchasing power in Indonesia.